Analisis Potensi dan Tantangan Pengembangan Pariwisata Alam Berbasis Ekowisata di Kawasan Air Merah Tangkiling, Kalimantan Tengah - Leviano Rafly; Lie Aditya Pratama; Muhammad Aji Fahreji; Fitriana Selvia (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Nature-based ecotourism has emerged as an important strategy for promoting sustainable regional development while preserving environmental resources. This study examines the development potential and challenges of ecotourism in the Air Merah Area, Tangkiling, Central Kalimantan, using the 4A destination development framework (attractions, amenities, accessibility, and ancillary services) and the Triple Bottom Line approach to sustainable tourism. The findings indicate that the area possesses considerable tourism potential, supported by attractive natural landscapes, increasing visitor arrivals, and positive economic contributions to local communities. Despite these advantages, tourism development remains constrained by limited road accessibility, inadequate electricity infrastructure, insufficient tourism facilities, and weak stakeholder collaboration. Analysis based on the Triple Bottom Line reveals that economic and social dimensions have shown positive progress through income generation and community participation, whereas environmental management remains relatively underdeveloped and requires more systematic conservation efforts. The study highlights the importance of integrating infrastructure improvement, institutional coordination, and sustainability-oriented management to strengthen the competitiveness and long-term viability of the destination. Sustainable ecotourism development in the Air Merah Area depends on balancing economic benefits, social inclusion, and environmental preservation within a coherent governance framework.